How do health services engage culturally and linguistically diverse consumers? An analysis of consumer engagement frameworks in Australia - Ashfaq Chauhan; Ramesh L. Walpola; Elizabeth Manias; Holly Seale; Merrilyn Walton; Carlene Wilson; Allan B. Smith; Jiadai Li; Reema Harrison (Wiley, 2021)
ABSTRACT Background Engagement frameworks provide the conceptual structure for consumer engagement in healthcare decision making, but the level to which these frameworks support culturally and linguistically diverse (CALD) consumer engagement is not known. Objective This study aimed to investigate how consumer engagement is conceptualised and operationalized and to determine the implications of current consumer engagement frameworks for engagement with CALD consumers. Method Altheide's document analysis approach was used to guide a systematic search, selection and analytic process. Australian Government health department websites were searched for eligible publicly available engagement frameworks. A narrative synthesis was conducted. Results Eleven engagement frameworks published between 2007 and 2019 were identified and analysed. Only four frameworks discussed engagement with CALD consumers distinctly. Organisational prerequisites to enhance engagement opportunities and approaches to enable activities of engagement were highlighted to improve CALD consumers' active participation in decision making; however, these largely focused on language, with limited exploration of culturally sensitive services. Conclusion There is limited discussion of what culturally sensitive services look like and what resources are needed to enhance CALD consumer engagement in high‐level decision making. Health services and policy makers can enhance opportunities for engagement with CALD consumers by being flexible in their approach, implementing policies for reimbursement for participation and evaluating and adapting the activities of engagement in collaboration with CALD consumers. Patient/Public Contribution This study is part of a wider 'CanEngage' project, which includes a consumer investigator, and is supported by a consumer advisory group. The study was conceived with inputs from the consumer advisory group, which continued to meet regularly with the project team to discuss the methodology and emerging findings.